Scientific approach to a selection in game tactics model in team sports - Trninic, S.; Papic, V.; Vukicevic, D. (Acta Kinesiologica, 2008)
A game tactics model in team sports is one of the factors that determines the success rate of the individual's and the whole team's accomplishments. Hence, a constructive selection of players based on a system of criteria which are features of the game tactics model formation is essential for the development of professional team sports and the teams' competition success rate. Such an approach is based on a teams' game tactics model analysis which is superior competition-wise, on anticipation of the direction of team sports development, on analysis of multiple causes of success and failure in each sports game. All these factors enable rational formations of a teams' game tactics model. Changes and the development of a player's potential, real qualities of a player and selection of a game tactics model is a scientific interdisciplinary and applied area. Formation of the game tactics model is a flexible process and it demands timely modifications during the preparation and the competition period. That is a functionally plastic process which is under the influence of feedback and/or new competitive experiences correcting all adequate changes in forming tactical systems and tactical combinations in team sports. Therefore, desirable changes in players' real quality, introducing to the team certain types of players which are necessary, are mutually intertwined and interact with modifications and transformations of game tactics models. The modifications of a game tactics model imply removal of inefficient and modeling of efficient tactical systems, tactical combinations and forms of game tactics.